Wing polymorphism in Anaphothrips graminum (Thysanoptera: Thripidae) - Minaei, Kambiz (Zootaxa, 2018)
Of the 83 species of Anaphothrips in the world (ThripsWiki 2018), only four are recorded in Iran so far (Alavi et al. 2018): A. microptera, A. obscurus, A. sineconus and A. sudanensis. Among these, A. sineconus was collected from Haloxylon persicum (Amaranthaceae) while the others are related to various grasses (Poaceae). Color and structural variation among and within the species of Anaphothrips have been demonstrated by several authors (Kudo, 1989, Nakao 1996, Mound & Masumoto 2009). In this paper a fifth species, A. graminum, is recorded from Iran based on specimens collected from grasses. The previously unknown micropterous morph of this species is described, as this is different in color from the macropterous morph, and in contrast to the original description the male has a pore plate on sternite VIII. The terminology used here follows Mound and Masumoto (2009). Most specimens are deposited in the Department of Plant Protection, Shiraz University, Shiraz, Iran (PPSU). Two females (one micropterous and one macropterous) are deposited in ANIC - the Australian National Insect Collection, CSIRO, Canberra.